Digitalization of traditional markets through tumbasin.id in facing industrial revolution 4.0: The Islamic business perspectives - Faizah, Fita Nurotul; Septiana, Vira (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2024)
This research explores how Tumbasin.id contributes to the digitization of traditional markets amidst the Fourth Industrial Revolution, focusing on its role in market development from the perspective of Islamic business ethics. Using a descriptive qualitative method involving interviews, observation, and documentation, the study reveals that Tumbasin.id innovatively connects traditional market traders and buyers in Semarang City. The tagline "shopping to the market without leaving the house" enhances its appeal, particularly during the COVID-19 pandemic. Tumbasin.id collaborates with traders to offer high-quality, affordable products, and its diverse services are specialized in different areas, encompassing both products and discounts. Regarding Islamic business ethics, Tumbasin.id demonstrates customer-oriented practices, transparency, fair competition, and consumer justice, fostering a business model aligned with ethical principles. Public interest statement This study provides insight to companies to identify issues in business development. The objective, to obtain alternative strategies that are more effective and efficient. As for other stakeholders can support business continuity by looking at risk projections. Not only that, this study also informs the transformation of traditional markets towards digital transformation towards going digital. Thus, making it easier for consumers and potential consumers in shopping by utilizing the internet. Article History Received 1/11/2023 | Final revised 2/2/2024 | Accepted 2/20/2024 | Online First 2/27/2024